Disability insurance screening and worker outcomes - Alexander Ahammer; Analisa Packham (W.E. Upjohn Institute for Employment Research, 2022)
We estimate the returns to more targeted disability insurance (DI) programs in terms of labor force participation and worker health. To do so, we analyze male workers after an acute workplace injury that experience differential levels of application screening. We find that when workers face tighter screening requirements, they are less likely to claim disability and are more likely to remain in the labor force. We observe no differences in any physical or mental health outcomes, including reinjury. Our findings imply that imposing stricter DI screening requirements has large fiscal benefits but does not yield any detectable health costs, on the margin.
Keywords: I38; I18; J18; J16; 330; disability insurance; retirement; health